Physical activity, memory function, and hippocampal volume in adults with Down syndrome - Peven, Jamie C.; Handen, Benjamin L.; Laymon, Charles M.; Fleming, Victoria; Piro-Gambetti, Brianna; Christian, Bradley T.; Klunk, William; Cohen, Ann D.; Okonkwo, Ozioma; Hartley, Sigan L. (Frontiers in Integrative Neuroscience, 2022)
Higher engagement in moderate-intensity physical activity (PA) is related to better cognitive functioning in neurotypical adults; however, little is known about the effect of PA on cognitive aging in adults with Down syndrome (DS). Individuals with DS have three copies of chromosome 21, which includes the gene involved in the production of the amyloid precursor protein, resulting in an increased risk for an earlier onset of Alzheimer’s disease (AD). The goal of this study was to understand the relationship between engagement in moderate PA, memory, and hippocampal volume in adults with DS. Adults with DS participated in an ancillary Lifestyle study linked to the Alzheimer’s Biomarkers Consortium for DS (ABC- DS; N = 71). A within-sample z-score memory composite was created from performance on the Cued Recall Test (CRT) and the Rivermead Picture Recognition Test. Participants wore a wrist-worn accelerometer (GT9X) to measure PA. Variables of interest included the average percentage of time spent in moderate PA and average daily steps. Structural MRI data were acquired within 18 months of actigraphy/cognitive data collection for a subset of participants (n = 54). Hippocampal volume was extracted using Freesurfer v5.3. Associations between moderate PA engagement, memory, and hippocampal volume were evaluated with hierarchical linear regressions controlling for relevant covariates [age, body mass index, intellectual disability level, sex, and intracranial volume]. Participants were 37.77 years old (SD = 8.21) and were 55.6% female. They spent 11.1% of their time engaged in moderate PA (SD = 7.5%) and took an average of 12,096.51 daily steps (SD = 4,315.66). After controlling for relevant covariates, higher memory composite score was associated with greater moderate PA engagement (β = 0.232, p = 0.027) and more daily steps (β = 0.209, p = 0.037). In a subset of participants, after controlling for relevant covariates, PA variables were not significantly associated with the hippocampal volume (all p-values ≥ 0.42). Greater hippocampal volume was associated with higher memory composite score after controlling for relevant covariates (β = 0.316, p = 0.017). More PA engagement was related to better memory function in adults with DS. While greater hippocampal volume was related to better memory performance, it was not associated with PA. Greater PA engagement may be a promising lifestyle behavior to preserve memory in adults with DS.